2019
DOI: 10.1111/bmsp.12184
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting dispersion in count data item response theory models: The Conway–Maxwell–Poisson counts model

Abstract: Count data naturally arise in several areas of cognitive ability testing, such as processing speed, memory, verbal fluency, and divergent thinking. Contemporary count data item response theory models, however, are not flexible enough, especially to account for overand underdispersion at the same time. For example, the Rasch Poisson counts model (RPCM) assumes equidispersion (conditional mean and variance coincide) which is often violated in empirical data. This work introduces the Conway-Maxwell-Poisson counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(93 citation statements)
references
References 53 publications
(68 reference statements)
0
93
0
Order By: Relevance
“…In particular, reliability estimates were the same (when rounded to three decimals) for both ordinal models (Rel(θ) = .961), and the CMPCM models (Rel(θ) = .969), clearly performed on par with these estimates. The slightly lower reliability of the RPCM as compared with the CMPCM models was due to the underdispersion in the data that is not taken into account by the RPCM (Forthmann et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, reliability estimates were the same (when rounded to three decimals) for both ordinal models (Rel(θ) = .961), and the CMPCM models (Rel(θ) = .969), clearly performed on par with these estimates. The slightly lower reliability of the RPCM as compared with the CMPCM models was due to the underdispersion in the data that is not taken into account by the RPCM (Forthmann et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This strong model assumption of equidispersion makes the model less useful than other members of the Rasch model family. Although subsequent methodological advances somewhat widened the applicability of the RPCM (Hung, 2012), only recently Forthmann et al (2019) showed how the original RPCM can be generalized into the Conway–Maxwell–Poisson Counts Model (CMPCM). The CMPCM is of similar flexibility as many linear latent trait models, as the mean is not directly related to the error variance.…”
Section: A Flexible Count Data Approach For Speeded C-testsmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that violin plots are interesting to show the fit of the test items. Considering the proposed method of analysis of residuals in the analyzed data, our results show that the model is not the best model for the data, so other models such as those of Hung (2012) and Forthmann, Gühne and Doebler (2019) can be studied in the future with this dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, real count data are often overdispersed (variance larger than mean) or underdispersed (variance smaller than mean). In either case, the inability of a model to account for underdispersion or overdispersion can cause standard errors to be biased downward or upward, thus under or over estimating the statistical significance of associated explanatory variables [8,9].…”
Section: Introductionmentioning
confidence: 99%